Physical activity aimed at weight loss the influence of the media on body aesthetics (Research, Society and Development, 2022)
The desire for the perfect body, following the standard that the media imposes, is one of the reasons people bet on physical activities, they seek quick results, but unfortunately this is not always the case, which can bring great inconvenience in all areas of life. your life. Therefore, the study aims to analyze the influence of the media on body aesthetics and how physical activity can promote healthy weight loss. Through an integrative literature review carried out through the SciELO, LILACS and MEDLINE databases, through the following DeCS: “weight loss”, “aesthetics”. Combined with each other by the Boolean AND operator. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme in the last twenty years. As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. From the initial search with the descriptors and Boolean operator defined, 402 studies were found in the selected bases and after applying the inclusion and exclusion criteria, 10 studies were selected to compose the review. Where they were categorized into two chapters, namely: The influence of the media on aesthetic standards, physical activity and healthy weight loss. We can conclude that social media has a great influence on the population, stimulating and manipulating them through photos and aesthetic procedures, alluding to the perfect body.